P-glycoprotein expression in oral lichen planus - Abhishek Jana; Jimcy Thomas; Pratiti Ghosh (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: Oral lichen planus (OLP) is a stress induced inflammatory condition with malignant potency. The mdr1 (multidrug resistance) is a stress gene overexpressed in cancerous conditions and its translated form, the p-glycoprotein efflux transporter is usually overexpressed with chemotherapy, leading to chemoresistance. OLP, a lesion with carcinogenic potency, is broadly classified into the asymptomatic reticular form and the aggressive erosive form. The objective of the study was to verify the expression level of p-glycoprotein in antifungal-treated and untreated reticular OLP, in untreated erosive OLP and erosive OLP patients treated with corticosteroid. Semi-quantitative reverse transcriptase polymerase chain reaction (SQ-RTPCR) and ELISA were performed on biopsy tissue samples to evaluate the mdr1 mRNA and protein expression of p-glycoprotein, respectively. The present study shows for the first time that mdr1 mRNA as well as its translated form p-glycoprotein are overexpressed in OLP subjects compared to healthy individuals. This overexpression is significantly higher in erosive than in reticular OLP patients, further confirming that the erosive form has higher risk for multidrug resistance. A higher expression is also observed in corticosteroid-treated erosive cases than similar untreated ones. The gradation of expression is in conformity with severity of the disease.